Pengaruh Ukuran Perusahaan dan Leverage terhadap Financial Distress dengan Pendekatan Altman Z-Score - Ramadhani, Nora Niza Dwi; Sari Andayani (Forum Kerjasama Pendidikan Tinggi, 2025)
This study aims to assess the influence of company size and debt-to-asset ratio on financial distress in healthcare companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2023. Financial distress is measured using the Altman Z-score method, while the independent variables consist of company size and the proportion of debt to total assets (DAR). This study adopts a quantitative method based on secondary data and applies a purposive sampling method, with 25 companies targeted as research subjects. Data analysis was performed through multiple linear regression using SPSS version 25 software. The results show that company size and leverage have a significant positive effect on financial distress. Company size has a significance value of 0.006 with a coefficient of 0.246, while leverage (DAR) shows a significance of 0.000 and a coefficient of 0.384. The coefficient of determination (R²) of 0.414 indicates that both independent variables are able to explain 41.4% of the variation in financial distress. Conclusion: Explains that company size and debt-to-asset ratio have a positive and significant impact on financial distress. This condition indicates that larger companies with higher leverage, as measured by the debt-to-asset ratio, tend to have higher Z-scores and indicate financial stability. This finding aligns with signaling theory, which assumes that a company's financial information serves as a positive signal to external parties.